Evaluating academic performance and scholarly impact of rectors of indonesia’s public universities: a dual bibliometric and scholastic analysis - Bayu Indra Pratama; Adi Wijaya; Budi Hermawan; Baharuddin; Purwoko (Cogent Education, 2024)
AbstractThis research conducted a combined bibliometric and scholastic analysis for characterizing and assessing rectors’ academic performance and scholarly impact at public universities in Indonesia. This bibliometric study evaluated the academic performance of 82 rectors of public universities in Indonesia from 93 initial candidates, focusing on 2706 data obtained through triangulation of open and verified data sources. The analysis showed male dominance, disparities in scientific productivity, and a tendency toward academic inbreeding. In citation analysis, the supremacy of natural science fields, especially Fisheries, Biology, Physics, and Engineering, becomes clear, showing a wider global impact than Accounting, Sociology, and Medicine. The richness and diversity of scientific areas are reflected in a higher range of citations, highlighting multidisciplinary integration and adaptation in responding to global challenges. These results trigger the need for intervention strategies to increase leadership diversity, scientific productivity, and gender equality in Indonesian public universities.